Metal-based nano-delivery platform for treating bone disease and regeneration - Liu, Yanhua; Xu, Zhengyi; Qiao, Mingxin; Cai, He; Zhu, Zhou (Frontiers in Chemistry, 2022)
Owing to their excellent characteristics, such as large specific surface area, favorable biosafety, and versatile application, nanomaterials have attracted significant attention in biomedical applications. Among them, metal-based nanomaterials containing various metal elements exhibit significant bone tissue regeneration potential, unique antibacterial properties, and advanced drug delivery functions, thus becoming crucial development platforms for bone tissue engineering and drug therapy for orthopedic diseases. Herein, metal-based drug-loaded nanomaterial platforms are classified and introduced, and the achievable drug-loading methods are comprehensively generalized. Furthermore, their applications in bone tissue engineering, osteoarthritis, orthopedic implant infection, bone tumor, and joint lubrication are reviewed in detail. Finally, the merits and demerits of the current metal-based drug-loaded nanomaterial platforms are critically discussed, and the challenges faced to realize their future applications are summarized.